Factors Influencing Crime Commission among College Graduate Prisoners - Romero, Jesine Rose; Pallega, Rowell; Alipoyo, Van Ryan I. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The goal of the study was to look into the factors that influence crime commission among college graduate inmates in the Dipolog and Dapitan City jails. The outcomes of the investigation were carried out using a quantitative approach. The required data was gathered using a purposive sampling strategy. The data was presented, analyzed, and interpreted using descriptive statistics. Highest number of college graduate incarcerated in Dipolog City Jail are graduate from Bachelor of Science in Criminology while in Dapitan City jail are graduate from Bachelor of Science in Education. Most of the college graduate prisoners in both city jails committed non-index crimes or non-violent crimes like violation of RA 9165, otherwise known as Comprehensive Dangerous Drugs Act of 2002 and less prone of committing index crimes or violent crimes like murder, homicide, rape, robbery and other violent crimes. Enmeshment in financial problems is the primary factors influencing crime commission among college graduate prisoners and followed by distrust in perceived support from family and friends. It is concluded that crimes can be committed by individuals regardless of his/her educational status.